Proses Adsorpsi Amonia dengan Karbon Aktif dari Cangkang Kelapa Sawit (Palm Shell) Teraktivasi H2SO4 - Wahyudi WR, Afit Sri; Dwi Oktaviani, Erika (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Activated carbon is a porous material that has a high surface area capable of adsorbing various substances. The process of making activated carbon uses palm oil shell biomass waste with a carbonization method and is activated using H2SO4. Activated carbon is used as an adsorbent in the Ammonia (NH3) adsorption process. Variations in the adsorption process were used, namely, H2SO4 activation concentration (5, 10, 15 and 20%) and adsorption contact time for (15, 30, 45, and 60 minutes). The optimum adsorption capacity of 12.97% was shown in the activated carbon adsorbent activated by 20% H2SO4 with a contact time of 30 minutes. The optimum result of reducing the NH3 concentration from 100 ppm to 50 ppm occurred at 15 and 20% activation with a contact time of 60 minutes. Variations in activation concentration and contact time affect the adsorption capacity so that NH3 can be absorbed by activated carbon.